Genetic Diversity of Army worm, Spodoptera mauritia Isolated from Kerala, India - Mashhoor, K.; Lazar, K.V.; Shanas, S.; Ramesh, N. (Research in Biotechnology, 2014)
The army worm Spodoptera mauritia is one of the major pests of paddy which is widely distributed in the Indian subcontinent, East and southern Asia and in the Australian region. Generally the army worms infest paddy crops of less than 20-25 days old. They are gregarious, defoliating the paddy and move from one field to other in large number like an army. The classification of Spodoptera species is mainly based on the structure of the male genitalia, antenna and the colour pattern of the wing. Here we report the partial coding sequence of cytochrome oxidase sub-unit I (COI) sequence of army worm isolated from Kerala, India which is identical to that isolated from Japan. This study highlights the geographical distribution and genetic diversity of army worm in paddy cultivating countries.